Improving Oral Health Knowledge Among Pregnant Women Using TikTok at the Jogoloyo Community Health Center in Jombang - Juanita Matkhurotin (Forum Ilmiah Teknologi dan Ilmu Kesehatan (FORITIKES), 2025)
Oral and dental health play a crucial role in maintaining overall well-being, particularly during pregnancy, when hormonal changes increase susceptibility to oral problems such as gingivitis and caries. However, awareness and knowledge of oral hygiene among pregnant women remain low, leading to a higher risk of oral diseases. Traditional health education methods often fail to attract sustained attention, highlighting the need for innovative, accessible approaches. This study aimed to evaluate the effectiveness of TikTok-based audiovisual education in improving oral health knowledge among pregnant women at the Jogoloyo Community Health Center in Jombang, Indonesia. A quasi-experimental study with a one-group pretest–posttest design was conducted on 58 pregnant women selected through purposive sampling. The intervention consisted of short TikTok videos (1–3 minutes) covering key topics such as oral hygiene maintenance, brushing time, and appropriate dental visits. Knowledge levels were measured using a validated questionnaire administered before and after the intervention. Data were analyzed using the Wilcoxon Signed Rank Test with a significance level of α = 0.05. The results demonstrated a significant improvement in oral health knowledge after the TikTok-based intervention. The mean pretest score was 36.59 ± 2.997, which increased to 66.24 ± 2.861 in the posttest, with a p-value of 0.001, indicating a statistically significant difference. Participants also showed notable progress in specific knowledge domains, including brushing time and dental check-up awareness. In conclusion, the study confirms that TikTok can serve as an effective and engaging platform for oral health promotion among pregnant women. Integrating social media–based audiovisual education into maternal health programs may enhance health literacy, accessibility, and engagement, offering a scalable alternative to conventional health education strategies in primary care settings.